Conductive material and preparation method thereof
Through the composite materials of porous carbon particles, zirconium nanoparticles and graphene, the problem of insufficient conductivity of lithium-ion battery conductive materials is solved, and higher conductivity and energy density of secondary batteries are achieved.
Patent Information
- Application Number
- CN202210002902.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-04
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-01-04
AI Technical Summary
The low conductivity of existing lithium-ion battery conductive materials limits the performance improvement of lithium-ion batteries, especially in terms of improving capacity, magnification and cycling performance.
Using a composite material of porous carbon particles, zirconium nanoparticles and graphene, the tiny pores on the surface of porous carbon particles are filled with zirconium nanoparticles, and graphene encapsulates porous carbon particles to form a layered structure, enhancing the conductivity, and optimizing the particles of the material through the preparation method. diameter and porosity.
The conductivity of conductive materials is significantly improved, the amount of conductive agent is reduced, and the amount of active materials for positive or negative electrode is increased, thereby improving the volume energy density and electrochemical performance of secondary batteries.
Smart Images

Figure BDA0003454240420000071 
Figure BDA0003454240420000081 
Figure HDA0003454240430000011
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy, and in particular relates to a conductive material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high operating voltage, large capacity, small size, light weight, and long cycle life. They are widely used in portable electronic products, electric bicycles, electric vehicles, energy storage, etc. Usually, lithium-ion batteries include positive electrodes, negative electrodes, separators, and electrolytes; among them, the dressing of the positive or negative electrode includes at least active materials, conductive agents, and binders; the conductivity of the conductive agent is one of the key factors affecting the performance of lithium-ion batteries. The materials that can be used for conductive agents are mainly carbon black, graphite, vapor-grown nanocarbon fibers, and carbon nanotubes; these materials have low conductivity, so the production usually adopts the method of increasing the proportion of conductive materials to maintain the performance of lithium-ion batteries, but the conductive agent itself is inert and cannot provide capacity, so increasing the proportion of conductive materials will reduce the energy density of lithium-ion batteries.
[0003] In summary, the low conductivity of existing conductive materials still has a significant restrictive effect on further improving the performance of lithium-ion batteries. It is necessary to develop more efficient conductive materials that can reduce the amount of conductive materials used while improving the overall conductivity of the positive and negative electrodes, thereby improving the capacity, rate and cycle performance of the battery. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a conductive material, which can significantly improve the conductivity of the conductive material through the design of the material and relative structure of each component.
[0005] The invention also provides a method for preparing the conductive material.
[0006] The present invention also provides a secondary battery having the conductive material.
[0007] According to one aspect of the present invention, a conductive material is provided, comprising:
[0008] Porous carbon particles; zirconium nanoparticles are distributed in the pores and on the surface of the porous carbon particles;
[0009] Graphene, wherein the graphene wraps the porous carbon particles.
[0010] According to a preferred embodiment of the present invention, at least the following beneficial effects are achieved:
[0011] (1) Graphene (sheet) can achieve "surface-point" contact with porous carbon particles, so that the resulting conductive material has a better conductive effect. That is, this contact mode makes it easier to form a conductive path inside the conductive material and between the conductive materials. Therefore, when the above conductive material is used to prepare a secondary battery electrode, the amount of conductive material can be reduced while ensuring the conductivity of the secondary battery electrode. At the same time, a conductive network can be constructed in the secondary battery electrode over a larger spatial span, achieving long-range conductivity on the entire electrode.
[0012] (2) Graphene is also a traditional conductive agent, but its planar structure will produce a steric hindrance effect on the transmission of active ions (such as lithium ions in lithium-ion batteries), especially at higher currents and rates. The present invention forms a layered structure (graphene nanosheets overlap each other during filtration and drying) by wrapping a composite intermediate of porous carbon particles and zirconium nanoparticles with graphene. The layered structure is a three-dimensional structure, which is equivalent to increasing the cross-sectional area of the conductive material, thereby improving the steric hindrance effect of graphene oxide.
[0013] (3) Zirconium nanoparticles fill the tiny pores on the surface of the porous carbon particles, reducing the impedance of the porous carbon particles, thereby improving the performance of the resulting conductive material.
[0014] (4) The conductive material provided by the present invention has extremely strong conductive properties. Therefore, in the positive and negative electrodes of the secondary battery, the amount of conductive agent used can be reduced, and the amount of positive electrode active material or negative electrode active material used can be increased, thereby greatly improving the volume energy density of the secondary battery.
[0015] In some embodiments of the present invention, the conductive material has a layered structure.
[0016] In some embodiments of the present invention, the porous carbon particles are soot particles.
[0017] In some embodiments of the present invention, the source of the soot particles is exhaust gas emitted by diesel vehicles.
[0018] In some embodiments of the present invention, the pretreatment of the soot particles includes sintering the collected soot particles.
[0019] In some embodiments of the present invention, the sintering atmosphere is air.
[0020] In some embodiments of the present invention, the sintering time is 4 to 8 hours.
[0021] In some embodiments of the present invention, the sintering temperature is 200-300°C.
[0022] The sintering is used to remove impurities.
[0023] The solid particles emitted by diesel vehicles are small in size and rich in carcinogenic organic substances such as polycyclic aromatic hydrocarbons. They are easily inhaled by humans and cause serious diseases. Collecting exhaust particles and reusing them is a sustainable development method. Diesel exhaust particles are mainly soot particles, which have conductive properties. Therefore, using soot particles to prepare the conductive material not only reduces battery costs, but also facilitates the secondary use of soot particles.
[0024] In some embodiments of the present invention, the particle size of the conductive material is 30 to 40 nm.
[0025] In some embodiments of the present invention, the porosity of the conductive material is 60-70%.
[0026] In some embodiments of the present invention, the specific surface area of the conductive material is 450 to 550 m 2 / g.
[0027] In some embodiments of the present invention, the mass ratio of the porous carbon particles to the zirconium nanoparticles is 5 to 10:1.
[0028] In some embodiments of the present invention, the graphene comprises graphene oxide.
[0029] In some embodiments of the present invention, the graphene sheet diameter is 200-260 nm.
[0030] In some embodiments of the present invention, the mass ratio of the sum of the mass of the porous carbon particles and the zirconium nanoparticles to the mass of the graphene is 3 to 5:1.
[0031] According to another aspect of the present invention, a method for preparing the conductive material is provided, comprising the following steps:
[0032] S1. adding the porous carbon particles to the dispersion of the zirconium nanoparticles, and after the reaction, calcining the resulting solid;
[0033] S2. Wet-mixing the solid obtained in step S1 with the graphene and removing the solvent.
[0034] In some embodiments of the present invention, the dispersant of the zirconium nanoparticle dispersion is at least one of ethanol and water.
[0035] In some embodiments of the present invention, in the dispersion of zirconium nanoparticles, the ratio of the zirconium nanoparticles to the dispersant is 1-2 g:100 mL.
[0036] In some embodiments of the present invention, the dispersion of zirconium nanoparticles is prepared by adding the zirconium nanoparticles into a dispersant and stirring for about 30 minutes.
[0037] In some embodiments of the present invention, the mass ratio of the porous carbon particles to the zirconium nanoparticles is 5 to 10:1.
[0038] In some embodiments of the present invention, the reaction temperature is 80-100°C.
[0039] In some embodiments of the present invention, the reaction time is 2 to 4 hours.
[0040] In some embodiments of the present invention, step S1 further comprises adding a binder to the dispersion of the zirconium nanoparticles before the reaction.
[0041] In some embodiments of the present invention, the binder includes at least one of glucose and sucrose.
[0042] In some embodiments of the present invention, the mass ratio of the binder to the porous carbon particles is 1:10-20.
[0043] The binder can improve the bonding between the zirconium nanoparticles and the porous carbon particles, so as to enable the former to fill into the pores of the latter or be loaded on the surface of the latter;
[0044] During the calcination in step S1, the binder may also be carbonized into loosely structured carbon to improve the conductivity of the conductive material.
[0045] In some embodiments of the present invention, in step S1, the solid obtained by the reaction is further washed and dried between the reaction and the calcination.
[0046] In some embodiments of the present invention, the washing solvent is acetone.
[0047] In some embodiments of the present invention, the drying temperature is about 50°C.
[0048] In some embodiments of the present invention, the drying time is 6 to 12 hours.
[0049] In some embodiments of the present invention, in step S1, the calcination temperature is 200-300°C.
[0050] In some embodiments of the present invention, in step S1, the calcination time is 2 to 4 hours.
[0051] In some embodiments of the present invention, in step S1, the calcination atmosphere is an air atmosphere.
[0052] In some embodiments of the present invention, the wet mixing method is: adding the solid obtained in step S1 to the organic dispersion of graphene.
[0053] In some embodiments of the present invention, the dispersant of the organic dispersion is at least one of acetone, ethanol and methanol.
[0054] In some embodiments of the present invention, the mass ratio of the solid obtained in step S1 to the graphene is 3 to 5:1.
[0055] In some embodiments of the present invention, the homogenization method is ultrasonication for 3 to 6 hours.
[0056] Since the conductive material provided by the present invention has excellent conductivity and its porosity is conducive to accommodating and passing active ions (lithium ions), the electrochemical performance of the obtained positive electrode sheet or negative electrode sheet can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0058] Figure 1 This is a scanning electron microscope image of the conductive material obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0059] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0060] Example 1
[0061] This embodiment prepares a conductive material, and the specific process is as follows:
[0062] A1. Collect soot particles from exhaust gas emitted by diesel vehicles, and then calcine these particles in air atmosphere for 4 hours at a calcination temperature of 200°C;
[0063] A2. Add 1 g of zirconium nanoparticles to 100 mL of ethanol, stir for 30 min, then add 10 g of soot particles obtained in step A1 and 1 g of glucose, and maintain the reaction at 80 ° C for 2 h;
[0064] A3. The mixture obtained in step A2 was separated into solid and liquid, and the solid was washed with acetone, and then the washed solid was dried at 50 ° C for 6h;
[0065] A4. The solid obtained in step A3 was calcined at 200 ° C in an air atmosphere for 2 h;
[0066] A5. Disperse 1 g of graphene oxide in 100 mL of acetone, add 3 g of the solid obtained in step A4, sonicate for 3 h, and then dry until the solvent evaporates.
[0067] The morphology of the conductive material obtained in this example is as follows Figure 1 As shown in the figure, it can be seen that the soot material is nearly spherical and the resulting conductive material has a porous structure.
[0068] Example 2
[0069] This embodiment prepares a conductive material, and the specific process is as follows:
[0070] A1. Collect soot particles from exhaust gas emitted by diesel vehicles, and then calcine these particles in air atmosphere for 5h at a calcination temperature of 220°C;
[0071] A2. 1.5 g of zirconium nanoparticles were added to 100 mL of ethanol, stirred for 30 min, and then 12 g of soot particles obtained in step A1 and 1 g of glucose were added, and the reaction was maintained at 85 ° C for 2.5 h;
[0072] A3. The mixture obtained in step A2 was separated into solid and liquid, and the solid was washed with acetone, and then the washed solid was dried at 50 ° C for 8h;
[0073] A4. The solid obtained in step A3 was calcined at 200 ° C in an air atmosphere for 2 h;
[0074] A5. Disperse 1 g of graphene oxide in 100 mL of acetone, add 3.5 g of the solid obtained in step A4, sonicate for 3 h, and then dry until the solvent evaporates.
[0075] Example 3
[0076] This embodiment prepares a conductive material, and the specific process is as follows:
[0077] A1. Collect soot particles from exhaust gas emitted by diesel vehicles, and then calcine these particles in air atmosphere for 6 hours at a calcination temperature of 240°C;
[0078] A2.2 g of zirconium nanoparticles were added to 100 mL of ethanol, stirred for 30 min, and then 14 g of soot particles obtained in step A1 and 1 g of glucose were added, and the reaction was maintained at 90 °C for 3 h;
[0079] A3. The mixture obtained in step A2 was separated into solid and liquid, and the solid was washed with acetone, and then the washed solid was dried at 50 ° C for 9h;
[0080] A4. The solid obtained in step A3 was calcined at 240 ° C in an air atmosphere for 3h;
[0081] A5. Disperse 1 g of graphene oxide in 100 mL of acetone, add 4 g of the solid obtained in step A4, sonicate for 3 h, and then dry until the solvent evaporates.
[0082] Example 4
[0083] This embodiment prepares a conductive material, and the specific process is as follows:
[0084] A1. Collect soot particles from exhaust gas emitted by diesel vehicles, and then calcine these particles in air atmosphere for 8h at a calcination temperature of 300°C;
[0085] A2.2 g of zirconium nanoparticles were added to 100 mL of ethanol, stirred for 30 min, and then 20 g of soot particles obtained in step A1 and 1 g of glucose were added, and the reaction was maintained at 100 °C for 3 h;
[0086] A3. The mixture obtained in step A2 was separated into solid and liquid, and the solid was washed with acetone, and then the washed solid was dried at 50 ° C for 12h;
[0087] A4. The solid obtained in step A3 was calcined at 300 ° C in an air atmosphere for 4 h;
[0088] A5. Disperse 1 g of graphene oxide in 100 mL of acetone, add 5 g of the solid obtained in step A4, sonicate for 6 h, and then dry until the solvent evaporates.
[0089] Comparative Example 1
[0090] This comparative example prepares a conductive material, which differs from Example 4 in that:
[0091] (1) does not include steps A2 to A4;
[0092] (2) In step A5, the solid obtained in step A4 is replaced by the solid obtained in step A1;
[0093] That is, the conductive material formed is graphene oxide wrapped carbon soot particles, and no zirconium nanoparticles are distributed in the pores or on the surface of the carbon soot particles.
[0094] Comparative Example 2
[0095] This embodiment prepares a conductive material, which is different from embodiment 4 in that:
[0096] (1) Step A5 is not included.
[0097] That is, the material obtained in step A4 is directly used as the conductive material, specifically a composite material formed by zirconium nanoparticles and carbon soot particles, but is not wrapped by graphene oxide.
[0098] Test example
[0099] This test example tests the impedance of the conductive materials prepared in the examples and comparative examples and the conventional conductive material acetylene black, wherein: the specific surface area and porosity are tested by BET, and the particle size is tested by a particle size analyzer.
[0100] The test results are shown in Table 1.
[0101] Table 1 Properties of the conductive materials obtained in Examples 1 to 4 and Comparative Examples 1 to 2
[0102]
[0103]
[0104] The results in Table 1 show that the conductive agent provided by the present invention significantly reduces the impedance due to the synergistic effect of the component materials and their mutual positional relationship; the lack of zirconium nanoparticles or graphene oxide in the conductive material will directly lead to an increase in impedance (a decrease in conductivity).
[0105] The particle size, specific surface area and porosity of the conductive materials obtained in Examples 1 to 4 and Comparative Examples 1 to 2 are similar, but the impedance of the conductive materials obtained in Examples 1 to 4 is significantly better than that of the conductive materials obtained in Comparative Examples 1 to 2. Finally, the performance of the commonly used conductive material acetylene black is significantly inferior to that of the conductive materials obtained in Examples 1 to 4. This indicates that the structure and composition of the conductive material provided by the present invention have a synergistic effect, which ultimately improves the conductive performance.
[0106] In addition, the present invention uses soot particles as porous carbon materials, which belongs to the secondary utilization of solid waste, conforms to the recycling economy, and has the advantages of low cost and simple preparation.
[0107] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A conductive material, characterized in that: include: Porous carbon particles; zirconium nanoparticles are distributed in the pores and on the surface of the porous carbon particles; Graphene, wherein the porous carbon particles are wrapped on the graphene; The porous carbon particles are soot particles; The particle size of the conductive material is 30 to 40 nm; The conductive material has a layered structure.
2. The conductive material according to claim 1, characterized in that The porosity of the conductive material is 60-70%.
3. The conductive material according to claim 1 or 2, characterized in that: The mass ratio of the porous carbon particles to the zirconium nanoparticles is 5 to 10:
1.
4. The conductive material according to claim 1 or 2, characterized in that: The mass ratio of the sum of the masses of the porous carbon particles and the zirconium nanoparticles to the mass of the graphene is 3 to 5:
1.
5. The method for preparing a conductive material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. adding the porous carbon particles to the dispersion of the zirconium nanoparticles, and after the reaction, calcining the resulting solid; S2. Wet-mixing the solid obtained in step S1 with the graphene and removing the solvent.
6. The preparation method according to claim 5, characterized in that: In step S1, the mass ratio of the porous carbon particles to the zirconium nanoparticles is 5 to 10:
1.
7. The preparation method according to claim 5, characterized in that: In step S1, the reaction temperature is 80-100°C.
8. The preparation method according to claim 5, characterized in that: In step S1, the reaction time is 2 to 4 hours.
9. The preparation method according to claim 5, characterized in that: Step S1 further includes adding a binder to the dispersion of the zirconium nanoparticles before the reaction.
10. The preparation method according to claim 9, characterized in that: The binder includes at least one of glucose and sucrose.
11. The preparation method according to claim 5, characterized in that: In step S1, the calcination temperature is 200-300°C.
12. The preparation method according to claim 5, characterized in that: In step S1, the calcination time is 2 to 4 hours.
Citation Information
Patent Citations
Production method of active material, and active material
CN101276908A
Porous carbon microsphere with surface covered with graphene, and preparing method and application of porous carbon microsphere
CN104528690A
Graphene nanosheet coated porous carbon fiber material and preparation method thereof
CN110957485A